Analysis of the mechanism of side impact of cars - Shapovalenko, V.; Шаповаленко, Владислав Олексійович (Харківський національний автомобільно-дорожній університет, 2023)
Globally, car crashes are the major cause of death, killing 1.2 million people, and despite improvements in car safety, forecasts indicate that car crash deaths will increase significantly by 2030 due to the increase in the number of cars. Such a trend requires an increase in passive safety in the design of cars. It is also necessary to consider with these factors the most popular segments of SUV cars, which during an accident create more dangerous consequences in the event of a side impact, taking into account the mass and dimensions parameters. Goal. The aim is to conduct an analysis of the side collision mechanism of cars of different mass and dimensional parameters. Taking into account the trends in the sale of cars, identifying the most popular classes of cars in Ukraine both on the new car market and on the second-hand market, to further identify problems in testing cars according to various certification protocols. Methodology. The approaches to solving the tasks used in the work are based on the use of statistical data and comparative analysis of various methodologies and certification protocols. Results. Considering that scientific studies of frontal impact are presented by the scientific community in the broadest form, the study of the side impact of two cars is currently a relevant direction, taking into account the global trend towards the production of cars in the SUV segment, which exceed passenger cars in terms of mass and dimensions. In a road accident with a side impact of a passenger car and an off-road vehicle of the SUV segment, we will get a large difference in the height of the primary impact, which is 250 millimeters. That is, all the energy of the impact to the side of the passenger car falls not on the safety bar, but 250 millimeters higher, which will nevitably lead to fatal injuries to the driver and passenger. Unfortunately, the European NCAP and the US National Highway Traffic Safety Administration use moving barriers that are similar in terms of mass and dimensions to an average passenger car. Originality. The obtained results of the analysis of the mechanism of the car side collision make it possible to evaluate the current trend of the automobile market in terms of passive safety and, in particular, to conduct certification tests for side impact in a new way. Practical value. The obtained results can be recommended when studying the structural features of preparing and conducting crash tests.
Аналіз механізму бокового зіткнення автомобілів
Keywords: passive safety; road accidents; deformation zone; injuries; road accident statistics; EuroNCAP; NHTSA.; пасивна безпека; ДТП; зона деформації; травматизм; статистика ДТП; 629.29.00; 10.30977/AT.2219-8342.2023.53.0.01